Sugarcane bagasse ozonolysis pretreatment: Effect on enzymatic digestibility and inhibitory compound formation - Travaini, Rodolfo; Otero, Marian Derly Morales; Coca, Mónica; Da-Silva, Roberto [UNESP]; Bolado, Silvia (Elsevier, 2013)
Sugarcane bagasse was pretreated with ozone to increase lignocellulosic material digestibility. Bagasse was ozonated in a fixed bed reactor at room temperature, and the effect of the two major parameters, ozone concentration and sample moisture, was studied. Acid insoluble and total lignin decreased whereas acid soluble lignin increased in all experiments. Pretreatment barely attacked carbohydrates, with cellulose and xylan recovery rates being >92%. Ozonolysis increased fermentable carbohydrate release considerably during enzymatic hydrolysis. Glucose and xylose yields increased from 6.64% and 2.05%, for raw bagasse, to 41.79% and 52.44% under the best experimental conditions. Only xylitol, lactic, formic and acetic acid degradation compounds were found, with neither furfural nor HMF (5-hydroxymethylfurfural) being detected. Washing detoxification provided inhibitor removal percentages above 85%, increasing glucose hydrolysis, but decreasing xylose yield by xylan solubilization. SEM analysis showed structural changes after ozonization and washing. © 2013 Elsevier Ltd.
Keywords: Enzymatic hydrolysis; Inhibitory compounds; Ozonolysis; Pretreatment; Sugarcane bagasse; 5 hydroxymethyl furfurals; Acid degradation; Acid soluble lignin; Enzymatic digestibility; Experimental conditions; Fermentable carbohydrate; Fixed bed reactor; Lignocellulosic material; Ozone concentration; Pre-Treatment; Raw bagasse; Recovery rate; Room temperature; SEM analysis; Structural change; Sugar-cane bagasse; Xylose yields; Acetic acid; Carbohydrates; Chemical reactors; Detoxification; Glucose; Molecular biology; Ozone; Ozonization; Sugar substitutes; Washing; Xylose; Bagasse; 5 hydroxymethylfurfural; acetic acid; bagasse; carbohydrate; cellulose; formic acid; furfural; glucose; lactic acid; lignin; lignocellulose; xylan; xylitol; xylose; biodegradation; bioreactor; detoxification; enzyme activity; fermentation; hydrolysis; inhibitor; ozone; pollutant removal; solubilization; sugar cane; temperature effect; biomass; concentration (parameters); enzyme degradation; fixed bed reactor; moisture; ozonation; ozonolysis; priority journal; qualitative analysis; reaction time; room temperature; scanning electron microscope; sugarcane; Acetic Acid; Chemical Reactors; Enzymatic Activity; Hydrolysis; Sugar Cane